If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5n + -6(7n + 6) = 9(-4 + 9n) Reorder the terms: -5n + -6(6 + 7n) = 9(-4 + 9n) -5n + (6 * -6 + 7n * -6) = 9(-4 + 9n) -5n + (-36 + -42n) = 9(-4 + 9n) Reorder the terms: -36 + -5n + -42n = 9(-4 + 9n) Combine like terms: -5n + -42n = -47n -36 + -47n = 9(-4 + 9n) -36 + -47n = (-4 * 9 + 9n * 9) -36 + -47n = (-36 + 81n) Add '36' to each side of the equation. -36 + 36 + -47n = -36 + 36 + 81n Combine like terms: -36 + 36 = 0 0 + -47n = -36 + 36 + 81n -47n = -36 + 36 + 81n Combine like terms: -36 + 36 = 0 -47n = 0 + 81n -47n = 81n Solving -47n = 81n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-81n' to each side of the equation. -47n + -81n = 81n + -81n Combine like terms: -47n + -81n = -128n -128n = 81n + -81n Combine like terms: 81n + -81n = 0 -128n = 0 Divide each side by '-128'. n = 0 Simplifying n = 0
| 2(2y-1)+1=y-3 | | w=228 | | 3(4+p)=39 | | -3(x-8)=2x-4-7x | | m-6=2m-3 | | 11+7x-10=8 | | S-2/5=4500 | | Y=.333x-4 | | 5x-10=115 | | (3x-90)/5=0 | | 2y=5x-3 | | -8x+10=-3x-20 | | -n+5(6n+1)=92 | | (-5x^2y)(-3x^12y^10)= | | 16x-15-9x=15 | | 20-2x+5x+20=9x-20 | | 7x^2/x^2 | | 186=k+93 | | 9x-13=4(2x+4)-3 | | 13x-4/48=3x-4/8 | | 8900=60x+5000 | | x^2-1/4x-15/64=0 | | 2(2x+4)=.75(24-8x) | | 100+36x=352 | | X+2+x-6= | | 5x-4(x-4)=6 | | 0.14y+0.06(y+3000)=1580 | | x+(16+2y)=73 | | 15m(m+2)=m-12 | | -7(3c+2)=4 | | 7-2x=2(-2-x) | | X^2+15x-39=0 |